(untitled) (European Journal of Pure and Applied Mathematics, 2018)
In this paper, the generalization of integral transform (GIT) of the func- tion Gf (t) is introduced for solving both differential and interodif- ferential equations. This transform generalizes the integral transforms which use exponential functions as their kernels and the integral trans- form with polynomial function as a kernel. The generalized integral transform converts the differential equation in us domain (the trans- formed variables) and reconvert the result by its inverse operator. In particular, if u = 1, then the generalized integral transform coincides with the Laplace transform and this result can be written in another form as the polynomial integral transform.